Edukasi Kesehatan Reproduksi Tentang Bahaya Seks Bebas di SMK Matorkis Padangsidimpuan - Rahmi Wahida Siregar; Muhammad Darwin Zulheddi; Meilani Harahap; Darma Afni Hasibuan; Nikmatul Khoiryah Pulungan (Bulletin of Community Engagement, 2024)
Sex education is one way to reduce or prevent sexual abuse, while promiscuous sexual behavior is relationships carried out by men and women with multiple partners which are shown in attitudes, feelings, desires and actions as a result of sexual desires and urges that are contrary to values ​​and norms in society. PKM activities last for one day, using the lecture method and using leaflet media. PKM's target is 40 students at Matorkis Padangsidimpuan Vocational School. The results of the PKM implementation showed that the majority of PKM participants' knowledge about adolescent reproductive health regarding the dangers of free sex was lacking, 28 participants (70%) experienced free sexual behavior. Educational efforts related to handling casual sex need to continue to be socialized to teenagers so that the impacts and dangers can be handled early and appropriately.